GENERASI MUDA MILLENIAL DALAM PERSPEKTIF ISLAM - Irfan Musadat (INCARE, International Journal of Educational Resources, 2021)
The purpose of this study is to enlighten readers, especially young people, about the millennial generation in Islamic perspective and strive to be able to make a positive contribution to the younger generation so that they are inspired to always act positively, constructively and not fall into destructive associations. In this paper the author tries to describe qualitatively about the Millennial generation in the view of Islam through the library research approach by collecting data through various kinds of literature and documents in the form of personal notes, books, journals and others related to the discussion of Millennial generation in the view of Islam. Millennials, also known as generation Y, are the demographic group after generation X. The term comes from millennials coined by two American historians and writers, William Strauss and Neil Howe in several of his books Millennial generation or generation Y is also known as generation me or echo boomers. Syekh Musthafa al Ghulayaini in his' idhoh he said "in the hands of the youth, the affairs of the ummah and the foot of the youth of the life of the ummat" he also added that "today's youth are the leaders of the future". From some of these adages it shows that there is so much hope for the future of youth because only by realizing the category of the young generation as a gate of life and as a cultural style can we understand our life and role.